Towards Sustainable Well-Being: From the CareSeeker and the Care-Giver: Challenges to the Implementation of Community-Based Health Planning and Services - Bougangue, Bassoumah; Mpawenimana, Abdallah Saidi (Universal Publishers - Boca Raton, Florida, USA, 2018)
Purpose: The objective of this paper was to explore the implementation challenges of the community-based health planning and services following persistent reports by the Ghana Statistical Service of poor clinical attendance, high incidence of maternal and child mortality and morbidity in the Region. Design/methodology/approach: This qualitative study used thirty in-depth interviews involving eight community health officers, eight community health volunteers and fourteen women receiving maternity care in the Yendi Municipality of the Northern Region of Ghana. Findings: Amongst other factors, the study observed poor co-ordination of healthcare interventions, cultural beliefs and practices, lack of incentives and poor community engagement as major setbacks to the progress of the policy. The policy should be carried out as part of the healthcare system by linking up with other healthcare interventions to increase access. There is the need for the policy to be re-visited and reformed to equip and mandate the facilities to provide skilled birth care. The community engagement aspect of the initiative should be given particular attention to make the healthcare services more accessible and acceptable to women to improve access to maternity care towards sustainable development. The research is done in the Yendi Municipality of the Northern Region of Ghana, it is original and not given to any other publisher